2010
DOI: 10.1100/tsw.2010.7
|View full text |Cite
|
Sign up to set email alerts
|

Long Noncoding RNAs, Chromatin, and Development

Abstract: The way in which the genome of a multicellular organism can orchestrate the differentiation of trillions of cells and many organs, all from a single fertilized egg, is the subject of intense study. Different cell types can be defined by the networks of genes they express. This differential expression is regulated at the epigenetic level by chromatin modifications, such as DNA and histone methylation, which interact with structural and enzymatic proteins, resulting in the activation or silencing of any given ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
130
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 135 publications
(132 citation statements)
references
References 128 publications
1
130
0
1
Order By: Relevance
“…These lncRNAs play important roles in tumor progression 18. LncRNAs have been confirmed to play a key role in gene epigenetic regulation, genome imprinting, X chromosome inactivation, and whole‐genome rearrangement 19, 20, 21. To the best of our knowledge, few differentially expressed lncRNAs have been reported to be associated with the tumorigenesis and progression of NPC.…”
Section: Discussionmentioning
confidence: 97%
“…These lncRNAs play important roles in tumor progression 18. LncRNAs have been confirmed to play a key role in gene epigenetic regulation, genome imprinting, X chromosome inactivation, and whole‐genome rearrangement 19, 20, 21. To the best of our knowledge, few differentially expressed lncRNAs have been reported to be associated with the tumorigenesis and progression of NPC.…”
Section: Discussionmentioning
confidence: 97%
“…Their expression is frequently linked to human cancer and other diseases (Panzitt et al 2007;Taft et al 2009). Some ncRNAs have critical functions in development (Caley et al 2010) and in the derivation of pluripotent stem cells (Loewer et al 2010). With this gene silencing approach suitable also for the generation of ncRNA-deficient cells, we provide a method that will help to unravel the cellular and molecular functions of these noncoding transcripts.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have focused on the regulatory roles of lncRNAs in several biological processes, such as chromosome inactivation, genomic imprinting and development (5)(6)(7). Recently, increasing reports have revealed that lncRNAs are frequently dysregulated in various human cancers, including bladder cancer (8,9).…”
Section: Introductionmentioning
confidence: 99%